Housing conditions of single mothers in Europe: the role of housing policies - Rense Nieuwenhuis; Hannah Zagel (European Societies, 2022)
This study investigates housing conditions of single mothers in the context of housing policies. We study single mothers' probability to experience housing deprivation, overcrowded housing, overburdening costs of housing, and neighbourhood problems across European countries. We consider the structural consequences of home ownership rates, and policies related to regulation of rental markets, housing benefits and housing prices. We apply a multi-level framework to EU-SILC data on 21,937 single mothers, from 195 country-years and covering 21 European countries from 2008 to 2017. First, we find a trade-off in the provision of free housing or housing at reduced rents, that helps to reduce housing cost overburden for single mothers, but is also associated with higher rates of housing deprivation, overcrowding and neighbourhood problems. Next, in contexts with stricter rental market regulation, single mothers' housing deprivation is lower. Higher housing benefits reduce the risk of housing deprivation as well as overcrowding, but in contexts where home ownership is common, single mothers tend to experience more overcrowding. Single mothers are more likely to report neighbourhood problems in societies where housing prices are high. Our findings suggest that factors within the control of policy makers can be beneficial to the housing conditions of single mothers.
doi:10.17605/OSF.IO/U8R9K
Keywords: 320; housing conditions; housing deprivation; single mothers; housing benefits; rental market regulation; housing prices; unitary and dual housing system